Piericidin A1 Blocks Yersinia Ysc Type III Secretion System Needle Assembly - Jessica M. Morgan (American Society for Microbiology, 2017)
ABSTRACT The type III secretion system (T3SS) is a bacterial virulence factor expressed by dozens of Gram-negative pathogens but largely absent from commensals. The T3SS is an attractive target for antimicrobial agents that may disarm pathogenic bacteria while leaving commensal populations intact. We previously identified piericidin A1 as an inhibitor of the Ysc T3SS in Yersinia pseudotuberculosis. Piericidins were first discovered as inhibitors of complex I of the electron transport chain in mitochondria and some bacteria. However, we found that piericidin A1 did not alter Yersinia membrane potential or inhibit flagellar motility powered by the proton motive force, indicating that the piericidin mode of action against Yersinia type III secretion is independent of complex I. Instead, piericidin A1 reduced the number of T3SS needle complexes visible by fluorescence microscopy at the bacterial surface, preventing T3SS translocator and effector protein secretion. Furthermore, piericidin A1 decreased the abundance of higher-order YscF needle subunit complexes, suggesting that piericidin A1 blocks YscF needle assembly. While expression of T3SS components in Yersinia are positively regulated by active type III secretion, the block in secretion by piericidin A1 was not accompanied by a decrease in T3SS gene expression, indicating that piericidin A1 may target a T3SS regulatory circuit. However, piericidin A1 still inhibited effector protein secretion in the absence of the T3SS regulator YopK, YopD, or YopN. Surprisingly, while piericidin A1 also inhibited the Y. enterocolitica Ysc T3SS, it did not inhibit the SPI-1 family Ysa T3SS in Y. enterocolitica or the Ysc family T3SS in Pseudomonas aeruginosa. Together, these data indicate that piericidin A1 specifically inhibits Yersinia Ysc T3SS needle assembly. IMPORTANCE The bacterial type III secretion system (T3SS) is widely used by both human and animal pathogens to cause disease yet remains incompletely understood. Deciphering how some natural products, such as the microbial metabolite piericidin, inhibit type III secretion can provide important insight into how the T3SS functions or is regulated. Taking this approach, we investigated the ability of piericidin to block T3SS function in several human pathogens. Surprisingly, piericidin selectively inhibited the Ysc family T3SS in enteropathogenic Yersinia but did not affect the function of a different T3SS within the same species. Furthermore, piericidin specifically blocked the formation of T3SS needles on the bacterial surface without altering the localization of several other T3SS components or regulation of T3SS gene expression. These data show that piericidin targets a mechanism important for needle assembly that is unique to the Yersinia Ysc T3SS.